Description of a new diatom species—Microcostatus dexteri sp. nov.—from terrestrial habitats in southern Poland - Jadwiga, Stanek-Tarkowska; Antonina, Czyż Ewa; Mateusz, Rybak (Phytotaxa, 2021)
A new Microcostatus species was found during a study focusing on diatoms present on soils and among terrestrial mosses. Unlike most known European species of this genus, it has easily distinguishable striae under the light microscope and a distinct central area. Additionally, the newly described species shows lack of conopeum and pseudoconopeum. A detailed morphological characterisation using light and scanning electron microscopy of a new species from the genus Microcostatus and comparison to the most similar taxa are given.